GRAPPLING WITH THE MODEL MINORITY MYTH: ASIAN AMERICAN FOOD BLOGGERS’ ACTIVISM THROUGH BLACK LIVES MATTER ON INSTAGRAM. - Dejmanee, Tisha (AoIR Selected Papers of Internet Research, 2023)
While Asian American food bloggers constitute an overrepresented racial minority within the predominantly white food blogosphere, food blogs rarely constitute productive spaces for discussing or building community around Asian American experiences even when published by Asian American bloggers. This study addresses the need for further intersectional analyses of food blogs that specifically take race into account as it explores the racial discourses generated by Asian American food bloggers participating in Instagram conversations around #BlackoutTuesday and Black Lives Matter in 2020. I find that #BlackoutTuesday authorised the discussion of race in a way that was not previously visible in the food blogosphere – for instance, Asian American food bloggers used Instagram posts in these conversations to identify with the politicised identity term ‘Asian American’ which, in turn, inspired solidarity and action amongst the Asian American community in support of Black Lives Matter. However, Asian American food bloggers also perpetuated elements of the model minority myth, distancing the microaggressions they had experienced from the ‘more serious’ racism and threats faced by Black Americans rather than acknowledging their joint and precarious structural oppression. This data demonstrates that the racial experiences of Asian American food bloggers continue to be silenced or diffracted, largely due to the ways that Asian American participation in this digital culture is structured through assimilation and racial commodification. Yet, despite these limitations, this conversation has value in contributing to visibility around minority allyship within the Black Lives Matter movement while also challenging the premise of political silence by minority bloggers.